KELAYAKAN MULTIMEDIA PEMBELAJARAN INTERAKTIF DALAM MEMOTIVASI SISWA BELAJAR MATEMATIKA - Lilis Diah Kusumawati; nFn Sugito; Ali Mustadi (Balai Besar Guru Penggerak Jawa Timur, 2021)
Interactive multimedia is a technology that mediates the development of learning activities to make it more interesting and enjoyable so that it can motivate students to learn. This study aims to determine feasibility of interactive learning multimedia product in motivating student for fourth grade of elementary school to learn mathematics. The research method uses the concept of ADDIE models to develop products with five stages, 1) analyze; 2) design; 3) develop; 4) implement; and 5) evaluate. The result showed that the development of interactive learning multimedia is feasible used for motivating students in grade 4 to learn mathematics. The result of validation by material experts showed that the products developed reached a score of 43 so that it was included in the